Alfabetização científica em Geografia: uma análise da proposta curricular do município de Itaquaquecetuba - Silva, Gildo Gomes Da [UNIFESP] (2019)
The teaching of Geography has undergone didactic-pedagogical reformulations through the application of new methodologies and more specifically of the active methodologies for the construction of geographic knowledge. Since it was observed in a basic elementary school that most of the students in the 5th grade of Elementary School completed the first part of this modality of education and wound up to the 6th grade of elementary school without appropriating the main basic concepts of Geography such as: landscape, territory, region, place, space. It was proposed to conduct a qualitative documental research in which the municipal curricular proposal of Itaquaquecetuba was analyzed in order to investigate whether the curricular proposal of the first period of the Geography area contributes to the process of scientific literacy and construction of knowledge in this science. In order to do so, it was necessary to analyze the geography elaborated by the Municipal Department of Education of Itaquaquecetuba county, in order to corroborate whether the curricular proposal of Geography was in agreement with the expected objectives of the theoretical references that deal with this subject. A bibliographic review was carried out in the databases of the ERIC platform (Education Resource Information Center and in the database of the CAPES (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior) platform in which scientific articles, thesis and dissertations were collected, in addition, some works by authors who work on the formation of geographic concepts and the construction of significant knowledge through the application of active methodologies and Scientific literacy in the teaching of Geography were used as theoretical references. These works served as an epistemological apparatus for the theoretical foundation for this research. The collected and analyzed works made it possible as a foundation and theoretical foundation to corroborate the construction of science from a historical perspective and the importance of science as a social-historical construction. The accomplishment of the bibliographical revision enabled a conceptualization of literacy scientific and confirmation of the affirmation of its importance as an active methodology applied to the teaching of Geography as well as a (re) conceptualization of the main geographic concepts. In view of this, it can be seen that some conceptual gaps have been found in the curricular proposal of Geography for Elementary School in Itaquaquecetuba county both in relation to the curriculum conceptualization as well as the geographical concepts that are presented to the teachers through the curricular proposal. This determines the urgent need to construct a curricular pedagogical proposal that assures teachers the possibility of constructing together with the students of this grade of teaching, a scientific-practical-culture in the school.